The Use of Triphenyl Phosphonium Cation Enhances the Mitochondrial Antiplatelet Effect of the Compound Magnolol - Francisca Tellería; Santiago Mansilla; Diego Méndez; Magdalena Sepúlveda; Ramiro Araya-Maturana; Laura Castro; Andrés Trostchansky; Eduardo Fuentes (MDPI AG, 2023)
Although platelets are anucleated cells, they have fully functional mitochondria, and currently, it is known that several processes that occur in the platelet require the action of mitochondria. There are plenty of mitochondrial-targeted compounds described in the literature related to cancer, however, only a small number of studies have approached their interaction with platelet mitochondria and/or their effects on platelet activity. Recent studies have shown that magnolia extract and mitochondria-targeted magnolol can inhibit mitochondrial respiration and cell proliferation in melanoma and oral cancer cells, respectively, and they can also induce ROS and mitophagy. In this study, the effect of triphenylphosphonium cation, linked by alkyl chains of different lengths, to the organic compound magnolol on human-washed platelets was evaluated. We demonstrated that the addition of triphenylphosphonium by a four-carbon linker to magnolol (MGN4) considerably enhanced the Magnolol antiplatelet effect by a 3-fold decrease in the IC50. Additionally, platelets exposed to MGN4 5 µM showed several differences from the control including increased basal respiration, collagen-induced respiration, ATP-independent respiration, and reduced ATP-dependent respiration and non-mitochondrial respiration.